Sharp Curvature of Premolar Resulting in External Apical Root Resorption of the Neighbouring Molar - Özgür İlke Atasoy Ulusoy (Case Reports in Dentistry)
This case report describes an external apical root resorption resulted from the unusual root morphology of the neighbouring tooth. A 28-year-old female was referred to the department of endodontics with a complaint of intense pain in her maxillary second premolar tooth. The clinical and radiographical evaluation revealed an external apical resorption in the mesial root of the maxillary first molar, which shows close proximity to the severely curved root of the premolar. A successful root canal treatment of the premolar was performed using anticurvature filing method. However, molar tooth received no curative treatment. One-year followup of the apical external resorption did not show any progression. External apical root resorption affecting single permanent tooth may be induced from the pressure exerted during the eruption of the adjacent tooth with unusual root morphology. The preferred approach for the management of such apical resorption cases includes long-term observation and no curative treatment.